Toxic Solvent‐ and Additive‐Free Efficient All‐Polymer Solar Cells via a Simple Random Sequence Strategy in Both Donor and Acceptor Copolymer Backbones. Issue 1 (25th November 2019) - Jeong, Mingyu; Lee, Byongkyu; Cho, Yongjoon; Oh, Jiyeon; Lee, Sang Myeon; Lee, Jungho; Yang, Changduk
Abstract: It is extremely important to develop nontoxic solvent and additive‐processed high‐performance all‐polymer solar cells (all‐PSCs) that are suitable for printing preparation of large‐scale devices. Herein, it is demonstrates that a simple random copolymerization of two acceptor monomers (benzo[1, 2‐ c :4, 5‐ c ′]dithiophene‐4, 8‐dione (BDD) and 5, 6‐difluoro‐2H‐benzo[ d ][1, 2, 3]triazole (FTAZ)), alternating with Si atom‐containing benzo[1, 2‐ b :4, 5‐ b ′]dithiophene donor comonomer, forms a successful approach by which to synthesize donor copolymers with excellent solubility/processability for nontoxic‐solvent‐processed all‐PSCs. The incorporation of a higher degree of BDD in the backbone lowers the frontier energy levels, as well as redshifts, with higher absorption coefficients; however, it adversely affects solubility in a 2‐methyltetrahydrofuran (MeTHF). An impressive power conversion efficiency, of about 8.0%, is achieved from PJ25 (25 mol% BDD)‐based all‐PSC when paired with N2200‐F30 acceptor random copolymer by using MeTHF as the processing solvent without any additive. Another interesting point is that the air stability of the all‐PSCs increases with increasing FTAZ content due to strong noncovalent interaction and resistance to humidity and oxidation caused by the F‐atoms in FTAZ units. Not only does this study establish a structure–property–performance relationship through a series of structural, morphological, and electrical characterization techniques, but it also provides a promising and easy way to develop nontoxic‐solvent‐processed high‐performance all‐PSCs. Abstract : Random donor copolymers consisting of two (benzo[1, 2‐ c :4, 5‐ c ′]dithiophene‐4, 8‐dione and 5, 6‐difluoro‐2H‐benzo[ d ][1, 2, 3]triazole) accepting monomers and Si atom containing benzo[1, 2‐ b :4, 5‐ b ′]dithiophene donor comonomer are synthesized and characterized for nontoxic‐processed all‐polymer solar cells (all‐PSCs). Upon the optimal monomer composition, a power conversion efficiency of about 8.0% is achieved from all‐PSC fabricated from 2‐methyltetrahydrofuran processing solvent without any additive.